Structure evolution and microwave absorption properties of nickel nanoparticles incorporated carbon spheres. (December 2016) - Su, Zhibin; Tao, Jin; Xiang, Jianyong; Zhang, Yu; Su, Can; Wen, Fusheng
Graphical abstract: Highlights: Carbon spheres were prepared. Nickel nanoparticles were incorporated onto carbon spheres. The minimum reflection loss value was −20.3 dB at 14.4 GHz with a matching thickness of 9.0 mm for 40 wt.% composites. Abstract: Carbon spheres were obtained by hydrothermal synthesis using glucose as carbon source, and then nickel nanoparticles were incorporated on carbon spheres by reducing with hydrogen. The nickel nanoparticles (about 6 nm) with magnetic loss were uniformly dispersed on the surface of carbon spheres (200–400 nm) with dielectric loss. The few-layer graphene have been obtained on the carbon spheres by nickel catalysis. The minimum reflection loss value of −20.3 dB was observed at 14.4 GHz with a matching thickness of 9.0 mm for 40 wt.% composites. The nickel nanoparticles incorporated carbon spheres are a promising candidate for excellent microwave absorption materials.